NAVIGATING ECONOMIC TERMINOLOGY: PRACTICAL STRATEGIES FOR LOWER GRADE - Ergasheva Nargiza Ne’matullayevna; Askarov Farhod Rakhmatovich; Gofirova Bibisora; Gafurova Nodrirakhon; Erkinjonov Firdavsbek (Scholars Digest Publishing, 2024)
This article delves into the immersive journey of Grade 5 students as they engage in practical economic learning through experiential methods such as role-playing, simulation, field trips, and project-based learning. Through crafting wooden seats, sewn handkerchiefs, baking cookies, making plastic toys, and organizing a school auction, these students actively apply economic principles while contributing tangibly to their community. By utilizing the proceeds to purchase gifts for elderly care home residents, they demonstrate empathy and delve into concepts such as market failure prevention and external cost reduction. This study underscores the significance of early exposure to economic concepts, showcasing how young learners can play an instrumental role in societal welfare while acquiring essential vocabulary and critical thinking skills.
Keywords: Literature, economics, field trips, project-based learning.